Pengaruh Market Value Added, Return on Equity, dan Return on Assets terhadap Return Saham dengan Valuasi korporasi sebagai Variabel Intervening (Studi Empiris pada Perusahaan Pertanian Sub Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020 - 2024) - Nugroho, Rahmanda Eko; Naryoto, Pambuko (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study is to analyze the effect of market value added (MVA), return on equity (RoE), and return on assets (RoA) on stock returns. This relationship is tested with corporate valuation as a mediating variable. This study focuses on 12 plantation sub-sector entities listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The sample was selected using purposive sampling based on predetermined criteria. The quantitative approach includes regression analysis and Sobel's test for mediation. The research findings show that MVA, RoE, and RoA have a significant effect on corporate valuation, but do not indicate an effect on stock returns. Furthermore, corporate valuation is not able to act as a mediating variable in the relationship between market value added (MVA), return on equity (RoE), and return on assets (RoA) with stock returns in 12 plantation sub-sector entities listed on the Indonesia Stock Exchange for the period 2020–2024.